Longitudinal characterization of TK6 cells sequentially adapted to animal product-free, chemically defined culture medium: considerations for genotoxicity studies - Perez-Diaz, Noelia; Hoffman, Ewelina; Clements, Julie; Cruickshank, Rebecca; Doherty, Ann; Ebner, Daniel; Elloway, Joanne; Fu, Jianan; Kelsall, Joanne; Millar, Val; Saib, Ouarda; Scott, Andrew; et al. (Frontiers in Toxicology, 2023)
Introduction:In vitro approaches are an essential tool in screening for toxicity of new chemicals, products and therapeutics. To increase the reproducibility and human relevance of these in vitro assessments, it is advocated to remove animal-derived products such as foetal bovine serum (FBS) from the cell culture system. Currently, FBS is routinely used as a supplement in cell culture medium, but batch-to-batch variability may introduce inconsistency in inter- and intra-lab assessments. Several chemically defined serum replacements (CDSR) have been developed to provide an alternative to FBS, but not every cell line adapts easily and successfully to CDSR-supplemented medium, and the long-term effect on cell characteristics remains uncertain. Aim: The aim of this study was to adapt the TK6 cell line to animal-product free CDSR-supplemented medium and evaluate the long-term effects on cell health, growth, morphology, phenotype, and function. This included a provisional assessment to determine the suitability of the transitioned cell line for standardised genotoxicity testing using the “in vitro mammalian cell micronucleus test” (OECD TG 487). Materials and methods: Gradual adaptation and direct adaptation methodologies were compared by assessing the cell proliferation, size and viability every passage until the cells were fully adapted to animal-free CDSR. The metabolic activity and membrane integrity was assessed every 4-8 passages by PrestoBlue and CytoTox-ONE™ Homogeneous Membrane Integrity Assay respectively. A detailed morphology study by high content imaging was performed and the expression of cell surface markers (CD19 and CD20) was conducted via flow cytometry to assess the potential for phenotypic drift during longer term culture of TK6 in animal-free conditions. Finally, functionality of cells in the OECD TG 487 assay was evaluated. Results: The baseline characteristics of TK6 cells cultured in FBS-supplemented medium were established and variability among passages was used to set up acceptance criteria for CDSR adapted cells. TK6 were adapted to CDSR supplemented medium either via direct or gradual transition reducing from 10% v/v FBS to 0% v/v FBS. The cell growth rate was compromised in the direct adaptation and therefore the gradual adaptation was preferred to investigate the long-term effects of animal-free CDSR on TK6 cells. The new animal cells showed comparable (p > 0.05) viability and cell size as the parent FBS-supplemented cells, with the exception of growth rate. The new animal free cells showed a lag phase double the length of the original cells. Cell morphology (cellular and nuclear area, sphericity) and phenotype (CD19 and CD20 surface markers) were in line (p > 0.05) with the original cells. The new cells cultured in CDSR-supplemented medium performed satisfactory in a pilot OECD TG 487 assay with compounds not requiring metabolic activation. Conclusion: TK6 cells were successfully transitioned to FBS- and animal product-free medium. The new cell cultures were viable and mimicked the characteristics of FBS-cultured cells. The gradual transition methodology utilised in this study can also be applied to other cell lines of interest. Maintaining cells in CDSR-supplemented medium eliminates variability from FBS, which in turn is likely to increase the reproducibility of in vitro experiments. Furthermore, removal of animal derived products from cell culture techniques is likely to increase the human relevance of in vitro methodologies.